Calcium ionophore A23187 versus progesterone: induction of acrosome reaction in thawed and prepared cryopreserved semen samples - Ravikuppan, Gayatri; Arunkumar, Sowbarnika; Thanikachalam, Puvithra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Acrosome reaction facilitates fertilization and it can be induced in-vitro using various stimuli like progesterone, calcium ionophore A23187, prostaglandins, etc. We investigated the efficacy of calcium ionophore and progesterone in inducing acrosome reaction in prepared semen samples following cryopreservation, using fluorescein isothiocyanate- labelled Arachis hypogaea (peanut) agglutinin (FITC-PNA) as a marker. Methods: A prospective analysis was carried out on 10 normozoospermic semen samples collected between March and May 2025 at the department of reproductive medicine and andrology, Chettinad Super Speciality Hospital, Chettinad Academy of Research and Education. The collected semen samples were cryopreserved using rapid freezing method and subsequently after thawing, sperm preparation was carried out using direct swim-up method. The obtained post-wash was then subjected to capacitation and in-vitro induction of acrosome reaction using calcium ionophore A23187 and progesterone. The spermatozoa were stained with a fluorescent dye FITC-PNA and by examining under a fluorescent microscope, acrosome reacted and acrosome intact spermatozoa were scored. An independent t-test was performed to determine the statistical significance between the two groups. The statistical significance was set at p value <0.05. Results: Our study revealed a significant difference between calcium ionophore and progesterone in inducing acrosome reaction in frozen thawed spermatozoa. Calcium ionophore demonstrated a higher acrosome reaction rate when compared to progesterone (p value <0.001). Conclusions: The in-vitro induced acrosome reaction rate in frozen thawed spermatozoa is significantly higher with calcium ionophore when compared to progesterone.